Wednesday

April 23, 2014

April 23, 2014

Posted by **Roni** on Friday, March 25, 2011 at 11:58am.

- Calculus -
**MathMate**, Friday, March 25, 2011 at 9:53pmreplace x in the expression:

f(x)=1-e^(4-2x)

by 2 to get:

f(2)=1-e^(4-2*2)

=1-e^0

=1-1

=0

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Pre-Calculus - Composition of Functions If f(x) = 2x+1 find A. f o f(x) f(f(x...

Calculus - 22. Divide the expression before differentiating. F(x) = (8x^3 - 1...

Calculus - Solve: dy = [2+(y-2x+3)^0.5]dx The answer in the book is 4(y - 2x + 3...

math-calculus - solve for x. |3x-2| = |2x+5|+1 okay so for these one it be |3x-2...

math-calculus - solve for x. |3x-2| = |2x+5|+1 okay so for these one it be |3x-2...

Pre Calculus - Solve 2cos^2(2x)=1 I divided both sides by 2 and got this cos^2(...

calculus - solve for the second derivative and set to zero f"(x) = ((x^2-4)*sin(...

PRE CALCULUS - 8-12SIN^2X=4COS^2X SOLVE FOR X

math - if (2x-3):(y+4)=k where k is a constant and x=4 when y=2 then find x when...